EXAMINING CHANGES IN THE LEVEL AND SHAPE OF INCOME DISTRIBUTIONS IN INDIA, 2005-2012 (Proceedings of The International Conference on Economics and Development, 2017)
Though Indian economy since 1980s has expanded very rapidly, yet the benefits of growth remain very unevenly distributed. This is corroborated while examining the panel data from the India Human Development Survey for 2005 and 2012. We find that Gini as a measure of income inequality has increased from 0.52 to 0.53 between 2005 and 2012. While, income inequality in rural area has increased from 0.49 to 0.52, in urban area, the same has increased from 0.47 to 0.49 during the same period. Adding to this, based on a recent distribution analysis tool, “ABG” the paper focuses on local inequality, which summarizes the shape of inequality in terms of three inequality parameters (α, β and γ) to examine how the income distributions have changed over time. Here, the central coefficient (α) measures inequality at the median level, with correction parameters at the top (β) and bottom (γ). The results reveal that at the middle of distribution (α), there is almost the same inequality in both the period, but the coefficients on the curvature parameters β and γ show that there is less inequality in 2005 at the extremes than in 2012 (α+β and α+γ are both smaller in 2005). Surprisingly, there is more inequality in rural India than its counterpart at both the extremes. Thus, this paper stresses the importance of inequality reduction in ending poverty and boosting shared prosperity in two core areas namely; progressive taxation and substantial social spending in education and health sectors compared to its present level.
Keywords: Income inequality; Isograph; Gini-coefficient; India